Some reflections on the concept application of essence over form in leasing operations in the lessee and lessor before and after IFRS 16 - Niyama, Jorge Katsumi; Mendes, Paulo César de Melo (REVISTA AMBIENTE CONTÁBIL - Universidade Federal do Rio Grande do Norte - ISSN 2176-9036, 2025)
Purpose: The present theoretical essay aims to assess the impacts of normative changes on the topic through a comparative study of the standards, emphasizing the approach related to “substance over form”. Methodology: The qualitative method was used to develop the study, through bibliographical and documentary research, where current scientific articles, books, accounting standards and procedures relating to the topic issued by national and international organizations were collected, which supported a comparative study on the changes made to the normative update on the accounting of leasing operations. Results: The results presented important points for the discussion, such as the main impacts caused by IFRS 16, the requirements for formalizing the leasing contract between the parties involved and the fact that the standard radically changes the concept of substance over form in the leasing. Contributions of the Study: It was concluded that, although IFRS 16 contributed to the quality improvement of the information presented by the lessees, in some cases the information does not represent the contract status reliably, due to the possibility of double accounting of the asset, as well as the differentiated adoption of the concept of substance over form in the lessee and lessor.